A SYSTEMATIC REVIEW ON ENHANCED TRANSMISSION AND EFFECTS OF SEVERE ACUTE RESPIRATORY SYNDROME CORONAVIRUS-2: AN INDIAN SCENARIO - PRASHANTH, KOTTHAPALLI; K, SUMANA; M PATIL, SHASHANK; RAMU, RAMITH (Asian Journal of Pharmaceutical and Clinical Research, 2020)
The outbreak of severe acute respiratory syndrome coronavirus-2 in Wuhan city of China has taken the entire world to an appalling situation with its detrimental effects on the mankind. Due to the facts on epidemiological and clinical features, it has become evident that the virus comprises several evolutionary factors that enhance its transmissibility and infection. In the absence of specific treatment options, many of the countries have implemented the confinement at varying levels and restrictions to control further infection. In the context, impact of confinement has affected different sectors including economy, social life, environment, health, and education, By virtue of the interrelated mechanism of functioning, these sectors have been ineffective, which, in turn, has affected the normal human lifestyle. This review emphasizes on such social sectors of India, where public life has been facing detrimental effects. It also highlights the facts that are responsible for the enhanced transmission of the virus. The review was initiated with a literature search using PubMed, Google Scholar, EMBASE, and Web of Science, where related keywords were used to collect 259 studies, and 82 of them were finalized based on relevance and information within. It was completed with equal contributions from all the authors in terms of preparing the manuscript.